Effect of awareness training to frontline health workers and the use of e-based technology on reporting of brucellosis cases in selected pastoral communities, Tanzania: a quasi-experimental study - Belinda Joseph Mligo; Calvin Sindato; Richard B Yapi; Mpoki Mwabukusi; Coletha Mathew; Ernatus M Mkupasi; Esron D Karimuribo; Rudovick R Kazwala (BMC, 2023)
Abstract Introduction Brucellosis is a serious community health problem and endemic disease in Tanzania in both humans and animals. Frontline health workers (FHWs) play a vital role in reporting and hence prevent and control brucellosis in rural settings. This study aims to evaluate the effect of awareness training to frontline health workers and use of electronic technology (e- technology) on reporting of brucellosis cases. Methods A quasi-experimental design was implemented in two pastoral communities in eastern part of Tanzania with one as control and another as treatment involving 64 FHWs who were purposively selected from May 2020 to December 2020. A total of 32 FHWs from treatment pastoral community were purposively selected for awareness training, rapid diagnosis using Rose Bengal test (RBT) and use of electronic technology (AfyaData app) for brucellosis reporting while nothing was done in control community. Before and after training information about their knowledge, attitude and practices were collected from all participants using a structured questionnaires uploaded in the mobile phone powered by AfyaData application. Blood samples were collected from 141 febrile patients attending the selected facilities in treatment community. Serum obtained from collected blood were analyzed using RBT and Competitive Enzyme Linked Immunosorbent Assay (c-ELISA) for brucellosis screening and confirmatory, respectively. Results from this analysis were reported back to the health facility using AfyaData app. Chi-square was used to analyze categorical variables and t-test and/Anova test was used to assess the effectiveness of the intervention. Results Results revealed that before the training majority of the participants were ignorant about brucellosis, although they had good attitude towards brucellosis prevention. Participant's awareness, practice and attitude increased significantly (p = 0.003, p = 0.001, p = 0.032) respectively, after the intervention. Total of 17(12.1%) patients were positive on RBT and four (2.8%) were confirmed by c-ELISA. AfyaData app was proven to provide quick reports regarding brucellosis in the study area. Conclusion The training program was effective in increasing the level of knowledge and practice about brucellosis. Electronic based technology (AfyaData app) improved the reporting of brucellosis cases. There is a need for the use of electronic based technology to improve timely management of brucellosis in pastoral communities. Also, continuous training on FHWs regarding the disease is needed to improved their awareness and practices.